Sarcoma‐Derived Extracellular Vesicles: Coupling Nanostructured Microchips with Covalent Chemistry Enables Purification of Sarcoma‐Derived Extracellular Vesicles for Downstream Functional Studies (Adv. Funct. Mater. 49/2020). (1st December 2020) - Dong, Jiantong; Zhang, Ryan Y.; Sun, Na; Hu, Junhui; Smalley, Matthew D.; Zhou, Anqi; Hua, Yue; Rothermich, Winston; Chen, Mengxiang; Chen, Jiayuan; Ye, Jinglei; Teng, Pai‐Chi; et al.
Abstract : In article number 2003237, Meiping Zhao, Hsian‐Rong Tseng, Yazhen Zhu, and co‐workers present a device for the purification of Ewing sarcoma‐derived extracellular vesicles (EVs) by coupling LINGO‐1 antibodies with the covalent chemistry‐mediated EV capture/release mechanism using a nanostructure‐embedded microchip. The purified EVs can be internalized by recipient cells to transfer the mRNA cargoes, highlighting the role of EVs as biological shuttles in intercellular communication.